Metropolitan competences: the unconstitutional attribution of the metropolitan mayor - Covilla Martínez, Juan Carlos (Universidad del Rosario, 2011)
The competences assigned to the administrative entity known in Colombia as “metropolitan area” (Law 128/1994) has been debated for a long time in the jurisprudence and among the governors. The present document seeks to illustrate the current situation of this debate and make some recommendations to improve the usage of these administrative entities, based on sociological and economical aspects. We will also explain how the powers given by law to the metropolitan mayors, the central city’s mayor of the metropolitan area, give theme the opportunity to govern indirectly on the action of the administrative entity.